Underage Use of Social Network Sites: It's About Friends - Barbovschi, Monica; Macháčková, Hana; Ólafsson, Kjartan (Cyberpsychology, behavior and social networking, 2015)
European self-regulation to ensure children's safety on social networking sites (SNS) stipulates that children should be old enough to use their services. However, a growing number of children are not. Drawing on data from the Net Children Go Mobile (NCGM) project (2012-2014), this study focuses on children aged 9-12 years, among whom 42% have a profile on Facebook, many with the explicit permission of their parents, despite the explicit policy allowing only children aged 13 years and older. Yet, such parental influence is not the only factor contributing to an underage child having a profile. Hierarchical logistic regressions were conducted in which the odds of having a profile on Facebook among children aged 9-12 years (N=1,723) were predicted. After controlling for demographic variables, Facebook use was connected to daily use of the Internet from home (bedroom and other places), looking for new friends online, and online disinhibition (e.g., being able to talk about different things on the Internet than when speaking to people face-to-face). In terms of parental mediation, restrictions lower the probabilities of an underage child having a SNS profile, while active parental mediation increases the odds. In addition to parental mediation, peer mediation increases the chances of underage Facebook use, indicating that children play a significant role in influencing each other in adoption of new technologies and applications. Finally, digital skills related to communication have a significant effect, suggesting an integrated adoption of communicative practices online. Daily use of mobile devices had no effect in the model.
Keywords: Friends; Humans; dítě; Child; Social Networking; sociální média; rodiče; Female; vztahy mezi rodiči a dětmi; lidé; Parents; přátelé; ženské pohlaví; Communication; Male; Social Media; Parent-Child Relations; komunikace; mužské pohlaví; sociální sítě